BEYOND THE BUSINESS LEADERSHIP: THE COACHING - Barrón Aráoz, Ricardo Ampelio (2010)
Tim Gallwey Harvard, explains in a simple way: “Coaching is unlocking the potential of a person to maximize their own performance. Is to help you learn instead of teach. Edgar Schein defines it as: A set of behavior by a coach (consultant) to help the client develop a new way of perceiving, feeling and behaving in situations that are defined by the customer as problematic. “In the sixties of the twentieth century in business circles, the term counseling slowly began to be replaced with the term “executive coaching.” In the decade of the nineties, the phenomenon of coaching was firmly established as an important method of management development for managers in the most important master global corporations.